The study on the relationship between venture capital, tolerance to failure, and enterprise innovation performance - Han, Jin; Chen, Minling; Chen, YanXin; Jing, Qinling; Wang, ShuangYan (Frontiers in Psychology, 2023)
Venture capital not only affects enterprise innovation decisions by providing funds, value-added services and allocating control rights, but also the psychological capital of venture capital can enhance its tolerance for failure in innovation activities of enterprises, and thus have a positive impact on innovation performance of enterprises. This paper uses multivariate and negative binomial regression models, propensity score matching method and Heckman treatment effect model to study the impact mechanism of venture capital on enterprise innovation performance, and the mediation role of venture capital’s tolerance for innovation failure in the relationship between the above two; this paper studies the moderating effect of the characteristics of heterogeneous venture capital institutions, such as joint investment strategies and geographical proximity, on the relationship between venture capital failure tolerance and enterprise innovation performance. The results show that venture capital can significantly improve its tolerance for enterprise innovation failure by holding shares and occupying seats on the board of directors of enterprises, thereby bring the increase of the innovation performance of enterprises; if joint investment strategy and close investment are selected, the tolerance of venture capital to innovation failure will have a more obvious effect on the promotion of enterprise innovation performance.